2015
DOI: 10.1039/c5bm00233h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled delivery of SDF-1α and IGF-1: CXCR4+ cell recruitment and functional skeletal muscle recovery

Abstract: Therapeutic delivery of regeneration-promoting biological factors directly to the site of injury has demonstrated its efficacy in various injury models. Several reports describe improved tissue regeneration following local injection of tissue specific growth factors, cytokines and chemokines. Evidence exists that combined cytokine/growth factor treatment is superior for optimizing tissue repair by targeting different aspects of the regeneration response. The purpose of this study was to evaluate the therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 74 publications
1
31
0
Order By: Relevance
“…Synthetic modification of fibrin with PEG improves the stability of the fibrin scaffold without changing its biochemical properties. We have previously used P‐fibrin gels to successfully achieve controlled delivery of various growth factors in vivo . Here we report on the feasibility of using stem cell‐loaded P‐fibrin gel for immediate burn wound coverage following surgical burn eschar excision via single application.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic modification of fibrin with PEG improves the stability of the fibrin scaffold without changing its biochemical properties. We have previously used P‐fibrin gels to successfully achieve controlled delivery of various growth factors in vivo . Here we report on the feasibility of using stem cell‐loaded P‐fibrin gel for immediate burn wound coverage following surgical burn eschar excision via single application.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled delivery of IGF-1 has also been demonstrated to recruit Pax7+ muscle cells into a scaffold, resulting in higher muscle formation [40]. Muscle stem cells may also be recruited through the delivery of SDF-1α, which was shown to increase the number of CXCR4+ cells, as well as promote angiogenesis in injured muscle [41]. In a study of volumetric muscle loss (VML), delivery of hepatocyte growth factor enhanced the contractile force of newly formed muscle by increasing the number of differentiated myoblasts and promoting angiogenesis [42].…”
Section: In Situ Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
“…Recently, a number of investigations have utilized PEG-based scaffolds (PEG-fibrinogen constructs) to deliver skeletal muscle-derived pericytes [128] and mesoangioblasts [129,130], and demonstrated that cell delivery in such materials promotes myogenic differentiation and skeletal muscle regeneration. Furthermore, controlled delivery of IGF-1 and SDF-1 using PEG-fibrin hydrogels also contributes to skeletal muscle regeneration [131,132]. In order to gain more precise control over building the cellular niche, PEG hydrogels that utilize maleimide crosslinking reaction chemistry also have been explored to culture C2C12 myoblasts in 3D [83].…”
Section: Delivery Matrices For Musc Engraftment and Functionmentioning
confidence: 99%